Using an Internet-Based Breast Cancer Risk Assessment Tool to Improve Social-Cognitive Precursors of Physical Activity. (August 2017) - Fowler, Stephanie L.; Klein, William M. P.; Ball, Linda; McGuire, Jaclyn; Colditz, Graham A.; Waters, Erika A.
Background . Internet-based cancer risk assessment tools might serve as a strategy for translating epidemiological risk prediction research into public health practice. Understanding how such tools affect key social-cognitive precursors of behavior change is crucial for leveraging their potential into effective interventions.Purpose . To test the effects of a publicly available, Internet-based, breast cancer risk assessment tool on social-cognitive precursors of physical activity.Methods . Women (N = 132) aged 40–78 with no personal cancer history indicated their perceived risk of breast cancer and were randomly assigned to receive personalized (www.yourdiseaserisk.wustl.edu ) or nonpersonalized breast cancer risk information. Immediately thereafter, breast cancer risk perceptions and physical activity-related behavioral intentions, self-efficacy, and response efficacy were assessed.Results . Personalized information elicited higher intentions, self-efficacy, and response efficacy than nonpersonalized information, P values < 0.05. Self-efficacy and response efficacy mediated the effect of personalizing information on intentions. Women who received personalized information corrected their inaccurate risk perceptions to some extent, P values < 0.05, but few fully accepted the information.Conclusion . Internet-based risk assessment tools can produce beneficial effects on important social-cognitive precursors of behavior change, but lingering skepticism, possibly due to defensive processing, needs to be addressed before the effects can be maximized.